Lay beliefs about hypertension among HIV-infected adults in Kenya. Issue 1 (1st March 2017) - Temu, Tecla M; Bahiru, Ehete; Bukachi, Fredrick; Bloomfield, Gerald S; Muiruri, Peter; Farquhar, Carey
Abstract : Objective: Hypertension affects 23% of Kenyans and is the most prevalent modifiable risk factor for cardiovascular disease. Despite this, hypertension awareness and treatment adherence is very low. We conducted a qualitative study to explore lay beliefs about hypertension among HIV-infected adults to inform the development of culture sensitive hypertension prevention and control program. Methods: Eight focus group discussions were held for 53 HIV-infected adults at the HIV clinic in Kenya. Results: Respondents had difficulties in describing hypertension. Hypertension was considered a temporary illness that is fatal and more serious than HIV. Stress was perceived as a main cause for hypertension with a large majority claiming stress reduction as the best treatment modality. Alcohol and tobacco use were not linked to hypertension. Obesity was cited as a cause of hypertension but weight control was not considered as a treatment modality even though the majority of our participants were overweight. Most participants did not believe hypertension could be prevented. Conclusion: Our findings suggest a limited understanding of hypertension among people living with HIV and points to an urgent need to integrate hypertension education programmes in HIV care facilities in Kenya. To effect change, these programmes will need to tie in the culture meaning of hypertension.